2016
DOI: 10.1038/srep31291
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic evidence for modulation of host inflammatory responses during febrile Plasmodium falciparum malaria

Abstract: Identifying molecular predictors and mechanisms of malaria disease is important for understanding how Plasmodium falciparum malaria is controlled. Transcriptomic studies in humans have so far been limited to retrospective analysis of blood samples from clinical cases. In this prospective, proof-of-principle study, we compared whole-blood RNA-seq profiles at pre-and post-infection time points from Malian adults who were either asymptomatic (n = 5) or febrile (n = 3) during their first seasonal PCR-positive P. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
95
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 39 publications
20
95
2
Order By: Relevance
“…Moreover, the efficacy of IPTp with SP to clear peripheral parasites and prevent new infections during pregnancy has been suggested to be compromised only in areas with > 90% prevalence of Pfdhps K540E mutation [33]. Taken together, these results suggest that immunoregulatory responses that reduce pathogenic inflammation and potentially the risk of anaemia [38] may be developed by pregnant women exposed to P. falciparum , as has been suggested for children [3941]. …”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the efficacy of IPTp with SP to clear peripheral parasites and prevent new infections during pregnancy has been suggested to be compromised only in areas with > 90% prevalence of Pfdhps K540E mutation [33]. Taken together, these results suggest that immunoregulatory responses that reduce pathogenic inflammation and potentially the risk of anaemia [38] may be developed by pregnant women exposed to P. falciparum , as has been suggested for children [3941]. …”
Section: Discussionmentioning
confidence: 93%
“…There are some exciting new areas of research that have begun to be explored in malaria. As mentioned above, remarkable discoveries are being made using multiparameter methods, transcriptomics and unbiased computational analyses of human immune responses . A logical progression would be to determine the influence of epigenetic modifications, such as DNA methylation and chromatin remodelling that regulate immune cell gene expression .…”
Section: New Areas Of Investigation and New Analytical Approachesmentioning
confidence: 99%
“…As mentioned above, remarkable discoveries are being made using multiparameter methods, transcriptomics and unbiased computational analyses of human immune responses. 156 A logical progression would be to determine the influence of epigenetic modifications, such as DNA methylation and chromatin remodelling that regulate immune cell gene expression. 157 In addition, the role of noncoding RNA (both human and P. falciparum-derived) is a rich area of exploration in human immunology.…”
Section: Ne W Are a S Of Inve S Ti G Ati On And Ne W Analy Tic Al Amentioning
confidence: 99%
“…Malaria infection inflicts host pathology by immune activation and increasing several proinflammatory mediators during the acute phase of the disease, whereas the host tries to circumvent these deleterious effects by increasing tolerance mechanisms to avoid tissue damage . The increase of tolerogenic FoxP3+ T regulatory cell (Treg) has been described in acute murine and human malaria infections .…”
Section: Introductionmentioning
confidence: 99%
“…Malaria infection inflicts host pathology by immune activation and increasing several proinflammatory mediators during the acute phase of the disease, [7][8][9][10] whereas the host tries to circumvent these deleterious effects by increasing tolerance mechanisms to avoid tissue damage. 10,11 The increase of tolerogenic FoxP3+ T regulatory cell (Treg) has been described in acute murine and human malaria infections. [12][13][14] Recent studies demonstrated that kynurenines (KYN), products of the tryptophan (TRP) catabolism pathway, induce the generation of Tregs via the activation of the aryl hydrocarbon receptor (AhR).…”
mentioning
confidence: 99%